Nutrient removal from leachate using horizontal subsurface constructed wetlands - Chew, Ai Ling (2006)
Leachate from sanitary landfill usually contains substantial amount of organic matters and inorganic substances, and has the potential to pollute ground and surface water. Treatability of leachate is dependent upon the composition of the leachate and the nature of the organic matters present. Constructed wetlands are treatment systems that treat the wastewater either above or below the soil surface. In this study, horizontal subsurface flow constructed wetlands had been applied. This study was conducted to investigate the removal of nutrient from landfill leachate by Typha angustifolia and to determine the treatability of horizontal subsurface constructed wetlands with different concentration of influent, hydraulic retention time (HRT), and sand to soil ratio comparison between the treatability of horizontal subsurface constructed wetlands with nd without vegetation is also carried out. Two laboratory-scale wetlands unit with one of e unit planted with cattails (Typha angustifolia) and another as control without any lants, were fed with primary treated landfill leachate and operated at hydraulic retention me of 1 – 5 days. The experiment is design by 2k factorial design to study the joint effect of the factors on the response. According to the study removal efficiency of nutrient from landfill in the form of ammoniacal nitrogen and nitrate by Typha angustifolia ranges from 2.6 – 88.9 %. Removal of BOD5 and COD by horizontal subsurface constructed wetlands with Typha angustifoilia ranges from 62.6 – 72.8 % and 64.5 – 85.7 % respectively. Removal efficiency of nutrient from landfill in the form of ammoniacal itrogen and nitrate by unplanted reactor ranges from 38.6 – 76.6 %. Removal of BOD5 nd COD by unplanted horizontal subsurface constructed wetlands ranges from 67.2 – 1.5 % and 60.3 – 72.5 % respectively. The HRT was found to affect the results, about 10 to 30% of differences in removal efficiency for longer HRT compare to shorter HRT.